Biomassa e nutrientes em plantios de erva-mate (Ilex paraguariensis A. St.-Hil.), no município de Nova Prata, RS - Berger, Gabriel (2006)
This study had as objective to quantify the total herbal tea biomass, to quantify the biomass produced in harvesting, to determine the nutrients amount in biomass compartments, to quantify the exported nutrients in herbal tea harvesting and to adjust mathematic models to quantify, due to equations, the harvest, residual and total biomass. Thirty plots were evaluated, totalizing 306 trees, where each circular plot had 44,18 m2 as area. In these plots, the biometric variables of each tree were measured: total height (ht), trunk diameters at 0,60 m above the soil (d 0.6 meters), height from the first branch or trunk, live crown lenght and crown projection rays. The harvest biomass, composed by leaves, stems and residue was evaluated too. After that, a plant located outside the plot was evaluated, that had the average dendrometric characteristics as the ones included in the plots. Later, each tree was cut at soil level, the leaves and stems, residues, wood, bark and roots weight were determined. The above ground biomass plus the roots biomass consisted in total biomass. The samples taken were dried in an oven to dry biomass and nutrients amount determination. The equations to estimate biomass, were done through SAS System version 8. The Stepwise method of independent variables selection was used, where at maximum 3 variables were included in the selected equations, and the partial R2 from the independent variable was higher to 1% to be considerable significant. The selection test from equations was done with and without intercept. The results showed by the equations without intercept were higher, being rejected these last ones. The nutrients amount determination was done in leaves and stem, wood, residues, bark and roots dried matter. The average fresh and dried biomass plus stems, sampled in the 30 units in kg/tree and kg/ha were: 7,849; 18577,34; 3,081; 7585,22 respectively. The average fresh and dried biomass residues in the 30 units in kg/tree and kg/ha were: 2,583; 6195,71; 1,009; 3052,01. The average fresh and dried leaves and stems biomass sampled in the 30 felled trees in kg/tree were: 7,713 and 3,174 respectively. The average fresh and dried biomass residues, sampled in 30 felled trees in kg/tree were: 2,708 and 1,358 respectively. The average fresh and dried biomass in wood, sampled in the 30 felled trees in kg/tree were: 13,609 and 6,785 respectively. The average fresh and dried roots biomass, sampled in the 30 felled trees were: 7,678 and 4,693 respectively. The total average fresh biomass per felled tree in kg/tree was 33,135. The total average dried biomass in kg/tree was 16,857. The estimated equations for different herbal tea dried biomasses were: wood biomass = 0.28329.rm + 0.07082.dh2; bark biomass =0,44728.lnm + 1,33596.im2; root biomass=2,32270.lnm + 12,81476.im2; residues biomass=0,34026.m 2,61245*ln2m + 0,43581.rm; leaves plus stems biomass=0,56043.ac + 2,06004.ln2d; total biomass=11,29406.rm + 0,10522.dh2. The total stand dried biomass was 41.078,03 kg/ha, being distributed: 16.654,49 kg/ha in the wood; 11.973,01 kg/ha in the roots; 7.582,22 kg/ha in leaves plus stems; 3.052,01 kg/ha in residues and 2.113,30 kg/ha in the bark. The macronutrients exported outside the stand follow this order: nitrogen > potassium > calcium > magnesium > sulphur > phosphorus. The components that show the higher amounts per hectare are: leaves plus stems (404,26 kg/ha), followed by roots (313,50 kg/ha), wood (149,93 kg/ha), residue (104,75 kg/ha) and bark (93,16 kg/ha). The micronutrients exported followed this order: iron > manganese > zinc > boron > cupper. The compartments that show the higher amounts per hectare are: roots (19,31 kg/ha), followed by leaves plus stems (6,43 kg/ha), wood (2,50 kg/ha), bark (2,24 kg/ha) and residues (1,08 kg/ha).